Are larger treasury issues more liquid? Evidence from bill reopenings - Michael J. Fleming (Federal Reserve Bank of New York, 2002)
This paper makes use of a natural experiment of the U.S. Treasury Department to examine the relationship between Treasury security issue size and liquidity. Treasury bills that were first issued with fifty-two weeks to maturity and then reopened at twenty-six weeks are shown to be more liquid than comparable maturity bills that were first issued with twenty-six weeks to maturity. The relationship is less pronounced when bills are on-the-run (the most recently auctioned bills of a given maturity) than when they are off-the-run, and persists when controlling for other factors that affect liquidity. The reopened bills are found to have higher yields (lower prices) than comparable maturity bills, showing that the indirect liquidity benefits of reopenings are more than offset by the direct supply costs.
Keywords: H63; G14; G12; 330; Treasury Market; Liquidity; Bid-ask spread; Trading volume; Issue size; Schatzpapier; Laufzeit; Gesamtwirtschaftliche Liquidität; Börsenumsatz; Bid-Ask Spread; USA